Peran Dan Strategi Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Di SMA IT Miftahul Ali Lendang Pengkores Dilihat Dari Dimensi Kepemimpinan Dan Dimensi Manajerial - Hasanudin, Hasanudin; Padlurrahman, Padlurrahman; Mashun, Mashun (Universitas Hamzanwadi, 2024)
This study aims to describe the role and strategy of school principals in improving the quality of education at Miftahul Ali IT High School from the leadership dimension and managerial dimension. This study uses a qualitative approach with a descriptive method. Data collection is carried out through observation, interviews and documentation. Data analysis is carried out with data reduction techniques, namely by using triangulation methods and sources. The results of this study show that there are 2 aspects of improvement made by school principals, namely as follows: a) the role of the principal as a leader , namely by guiding and directing educators in creating interesting learning methods, then the school principal tries to establish communication with stakeholders who through reprimands and greetings and hearing directly input from teachers and school employees on the problems being faced, in making decisions the principal implements an open democracy system through deliberation and joint decisions, the principal also becomes a good example through disciplined behavior at work. As for determining the achievement of the program, the principal conducts periodic supervision and evaluation of the learning process and learning tools and utilizes the results of supervision to further improve learning activities through coaching and direction from the principal and supervisors. and b) the role of the principal as a manager, is carried out by managing the school starting from planning the school work program at the beginning of the school year at the time of the work meeting by involving educators and education staff as well as the management of the Foundation and committees, the principal also participates in educators and education personnel in various training and coaching activities to support competence, then the principal also maintains facilities and infrastructure periodically. The findings of this study show that the principal has realized his role in improving the quality of education at SMA IT Miftahul Ali Lendang Pengkores, by taking improvement steps.